The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1080/20009666.2020.1811556
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal pathophysiology of SARS-CoV2 – a literature review

Abstract: SARS-CoV2 is a novel coronavirus responsible for causing COVID-19, first identified in the city of Wuhan, China and officially declared a pandemic by the World Health Organization. SARS-CoV2 expresses high affinity to human ACE2 receptors, including within the gastrointestinal tract. Patients with COVID-19 exhibit a wide spectrum of GI symptoms including anorexia, nausea, vomiting, abdominal pain, and abnormal liver function tests. Pathogenesis behind gastrointestinal symptoms caused by SARS-CoV2 has been post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 42 publications
0
20
0
2
Order By: Relevance
“…The composition of gut microflora in patients with COVID-19 and even recovered patients is unbalanced, which is characterized by the decrease of beneficial microbes and the increase of harmful ones ( Yeoh et al, 2021 ). These results suggest that the GI disorders caused by COVID-19 are mainly due to the destruction of intestinal mechanical barrier integrity, alteration of the intestinal microflora, and systemic inflammatory response to the virus ( Luo et al, 2021 ; Syed et al, 2020 ; Villapol, 2020 ). Therefore, it is recommended to properly add beneficial intestinal microbes, especially probiotics and prebiotics, which may enhance the intestinal barrier function, help to improve and alleviate the sequela of COVID-19 and accelerate the complete recovery of patients.…”
Section: Current Concerns and Suggestions On Sars-cov-2 Mutationmentioning
confidence: 92%
“…The composition of gut microflora in patients with COVID-19 and even recovered patients is unbalanced, which is characterized by the decrease of beneficial microbes and the increase of harmful ones ( Yeoh et al, 2021 ). These results suggest that the GI disorders caused by COVID-19 are mainly due to the destruction of intestinal mechanical barrier integrity, alteration of the intestinal microflora, and systemic inflammatory response to the virus ( Luo et al, 2021 ; Syed et al, 2020 ; Villapol, 2020 ). Therefore, it is recommended to properly add beneficial intestinal microbes, especially probiotics and prebiotics, which may enhance the intestinal barrier function, help to improve and alleviate the sequela of COVID-19 and accelerate the complete recovery of patients.…”
Section: Current Concerns and Suggestions On Sars-cov-2 Mutationmentioning
confidence: 92%
“…Notably, impaired tryptophan homeostasis in Ace2-deficient mice decreases antimicrobial peptide generation resulting in an altered intestinal microbiome [110]. With ACE2 being highly expressed in enterocytes, it is therefore not surprising that intestinal infections with SARS-CoV-2 would promote gastrointestinal symptoms like diarrhea [111].…”
Section: The Challenge Of Determining Causality In Epidemiologymentioning
confidence: 99%
“…Moreover, a recent study demonstrated that both ACE2 and TMPRSS2 genes were abundantly expressed in enterocytes of the lower gastrointestinal (GI) tract, whilst also exhibiting co-expression with TMPRSS4, particularly in the small intestine ( 16 ). Of note, whereas COVID-19 presentation usually includes fever, cough, pulmonary/respiratory symptoms, and loss of taste and smell ( 17 , 18 ), an increasing number of studies has also reported GI-related symptoms (e.g., diarrhoea, nausea and vomiting) in patients with COVID-19 ( 19 - 21 ). Indeed, a proportion of these patients with extra-pulmonary symptoms do not exhibit other respiratory symptoms ( 22 ).…”
Section: Introductionmentioning
confidence: 99%